Germanistik in Lateinamerika Entwicklungen und Tendenzen - Gruhn, Heike (Universitätsverlag Göttingen, 2021)
Latin America and the German-speaking countries of Central Europe have for a long time maintained multifaceted and dynamic relations. This close interaction has also had a significant impact on the history and present of institutional Germanic studies in Latin America. There are, however, country-specific differences: while in the case of some locations there is only a rudimentary area of Germanic Studies, in others it is quite broadly established. The main purpose of this volume is to trace the existing diversity. The idea for the publication emerged during the 16th Congress of the Latin American Association of Germanists (ALEG) in Buenos Aires in December 2017. Within the framework of the section "History of Germanic Studies", the need for an anthology with contributions in German became evident, in which the developments and perspectives of Germanic studies in the various Latin American countries and regions are reviewed and discussed. Academics from across Latin America agreed to share insights and findings on the aims and foci of Germanic studies for the book project to be realized. Since the institutional framework of the discipline varies widely in Latin America, the initiators assume a broad concept of Germanic studies that encompasses the teaching and research of literary and cultural studies, as well as linguistic and translation studies, teacher training and the teaching of the German language itself. The anthology combines a total of 22 articles from eleven countries, written by 39 authors, and thus provides a broad and diverse view of the situation of Germanistic studies in Latin America. It includes overviews and analyses from Argentina, Bolivia, Brazil, Chile, the Dominican Republic, Ecuador, Colombia, Mexico, Paraguay, Uruguay and Venezuela.